Evaluation and selection of an optimum material for coil tubes in CT drilling technology for hard rocks in mineral exploration - Lagat, Christopher Kipchumba (Curtin University, 2015)
The PhD study aimed at evaluating and selecting optimum material for coiled tubes in CT drilling technology for hard rocks in mineral exploration. Numerical computer modelling, using Abaqus and Hypersizer software packages, was undertaken to analyse stress distribution and investigate the effect of fibre orientation and stacking sequence of fibre layers that constitute the composite tube laminate. Cyclic bending tests using a fatigue testing machine and mechanical tensile tests were carried out to validate the simulation results.